Training of HOTS-Based Teaching Factory to Improve Teachers’ Competencies at SMK Muhammadiyah 6 Jakarta - Wahjusaputri, Sintha; Bunyamin (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
This training aims at developing teachers’ professionalisms and competencies that consist of analyzing, evaluating, creativity, and being able to conclude or solving problems at SMK Muhammadiyah 6, Jakarta. The training activities were conducted from 10 to 12 February 2020 at SMK Muhammadiyah 6 Jakarta. The number of participants who participated in the training was 17 people. The training uses lecture, discussion, demonstration, and practice methods. After the training, the participants practiced teaching factory topics based on HOTS and assisted by the PKM Team. The training resulted that the participants were satisfied that they showed the presence of enthusiasts at each training meeting. Participants presented a very well assessment of the attitude of activeness, cooperation, and responsibility towards mastering the development of HOTS-based teaching factories. The supporting factors for the PKM activities are (1) the availability of the team resources, (2) the enthusiasm of the participants, and (3) the support of the principal.